Stability Analysis and Design of Time-Varying Nonlinear Systems Based on Impulsive Fuzzy Model - Yuangan Wang; Honglin Yu; Xiaohong Zhang; Dong Li (Discrete Dynamics in Nature and Society)
This paper develops a general analysis and design theory for nonlinear time-varying systems represented by impulsive T-S fuzzy control model, which extends conventional T-S fuzzy model. In the proposed, model impulse is viewed as control input of T-S model, and impulsive distance is the major controller to be designed. Several criteria on general stability, asymptotic stability, and exponential stability are established, and a simple design algorithm is provided with stability of nonlinear time-invariant systems. Finally, the numerical simulation for the predator-prey system with functional response and impulsive effects verify the effectiveness of the proposed methods.